PLEXQ: Towards a playful experiences questionnaire - Boberg, Marion; Karapanos, Evangelos; Holopainen, Jussi; Lucero, Andrés (My University, 2015)
Playfulness is an important, but often neglected, design quality for interactive products. This paper presents a first step towards a validated questionnaire called PLEXQ, which measures 17 different facets of playful user experiences. We describe the development and validation of the questionnaire, from the generation of 231 items, to the current questionnaire consisting of 17 constructs of playfulness, each measured through three items. Using PLEXQ we discuss the nature of playfulness by looking at the role of age, gender, and product type in one's proclivity to experience playfulness differently. Finally, we reveal a four-factor structure of playfulness and discuss the implications for further theory development.
Keywords: Playful experiences; Scale development; User experience